2014
DOI: 10.1089/wound.2013.0448
|View full text |Cite
|
Sign up to set email alerts
|

Electrostimulation: Current Status, Strength of Evidence Guidelines, and Meta-Analysis

Abstract: Significance: Delayed healing of skin wounds is a serious problem for the patients, clinicians, and society. The application of interventions with proven effectiveness to increase wound healing is relevant. Recent Advances: This article summarizes the results of effect studies with the application of electrostimulation (ES) as additional treatment to standard wound care (SWC). Therefore, five published narrative reviews are discussed. In addition, 15 studies with a clear randomized controlled trial design are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0
9

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 33 publications
3
46
0
9
Order By: Relevance
“…A previous in vitro study revealed that ES could also reduce inflammation (Cho et al, 2000). In results similar to the effect of vibration, previous studies have also shown that ES accelerates wound healing in pressure, ischemic and diabetic ulcers (Eriksson et al, 1981;Goldman et al, 2003;Koel and Houghton, 2014).…”
Section: Introductionsupporting
confidence: 69%
“…A previous in vitro study revealed that ES could also reduce inflammation (Cho et al, 2000). In results similar to the effect of vibration, previous studies have also shown that ES accelerates wound healing in pressure, ischemic and diabetic ulcers (Eriksson et al, 1981;Goldman et al, 2003;Koel and Houghton, 2014).…”
Section: Introductionsupporting
confidence: 69%
“…115 SRs that evaluated the effect of EST on all types of chronic wounds were generally well done and included the majority of available research that had been published at the time of the review. 102,[104][105][106]109 Only one of the eight SRs that focused specifically on the effects of EST or other physical modalities, did not support the use of EST for wound healing. 114 In the Cochrane review published in 2001, because of different outcomes measured at several time points, the meta-analysis evaluating the pooled effect of EST included only one RCT.…”
Section: Discussionmentioning
confidence: 99%
“…94,[97][98][99][101][102][103] Critical appraisal of SRs and meta-analyses Table 4 outlines the details of 18 reviews that have been published in the literature on the effect of EST on wound healing. 5,10,14,15,[104][105][106][107][108][109][110][111][112][113][114][115][116] Eight of the reviews completed at least some form of meta-analysis. 10,15,[104][105][106][107][108][109] Three other reports stated that although a meta-analysis was planned, none was done because of heterogeneity of included studies.…”
Section: Narrative Reviewsmentioning
confidence: 99%
See 2 more Smart Citations